Self-Acceptance of Chronic Caused Failure Patients That Have a Hemodialysis in Medan - Cholina Trisa Siregar; Mia Rhamayani (Caring: Indonesian Journal of Nursing Science, 2019)
Chronic kidney failure patients undergoing hemodialysis undergo physical and psychological changes. Self-acceptance is a person's ability to have a realistic assessment of advantages and disadvantages. This study aims to describe self-acceptance in patients with chronic renal failure undergoing hemodialysis in the RSUD Dr. Pirngadi Medan. The study population was patients with chronic renal failure who underwent hemodialysis at the RSUD Dr. Pirngadi Medan. The sample of this study amounted to 106 people. The sampling technique uses non probability sampling, namely, purposive sampling. The inclusion criteria for the study sample were chronic kidney failure patients who underwent hemodialysis who were in consciousness compos mentis. Data collection was conducted in April-May 2017. Data were analyzed by descriptive statistical analysis. The results of the study obtained data that 12 people were at high self-acceptance (11.3%), 80 people were at moderate self-acceptance (75.5%), and 14 people were at low self-acceptance (13.2%). Based on the results of the study it can be concluded that patients with chronic renal failure undergoing hemodialysis in the RSUD Dr. Pirngadi Medan has a good self-acceptance, ie the patient accepts his condition even though he has to undergo hemodialysis for life. Researchers expect that nurses can provide emotional support and motivation to patients to improve patient self-acceptance.